Assessing the Relationship Between Leukocyte Telomere Length and Cancer Risk/Mortality in UK Biobank and TCGA Datasets With the Genetic Risk Score and Mendelian Randomization Approaches - Gao, Yixin; Wei, Yongyue; Zhou, Xiang; Huang, Shuiping; Zhao, Huashuo; Zeng, Ping (Frontiers in Genetics, 2020)
Background: Telomere length is an important indicator of tumor progression and survival for cancer patients. Previous work investigated associations between genetically predicted telomere length and cancers; however, the types of cancers investigated in those studies were relatively limited or the telomere-length associated genetic variants employed often came from genome-wide association studies (GWAS) with small sample sizes. Methods: We constructed the genetic risk score (GRS) for leukocyte telomere length based on 17 associated genetic variants available from the largest telomere-length GWAS up to 78,592 individuals. Then, a comprehensive analysis was undertaken to evaluate the association between the constructed GRS and the risk or mortality of a wide range of cancers (i.e. 37 cancers in UK Biobank and 33 cancers in TCGA). We further applied the two-sample Mendelian randomization (MR) to estimate the causal effect of leukocyte telomere length on UK Biobank cancers via summary statistics. Results: In the UK Biobank dataset we found the GRS of leukocyte telomere length was associated with the decreased risk of nine types of cancer (i.e. significant association with multiple myeloma, chronic lymphocytic leukemia, kidney/renal cell cancer, bladder cancer, malignant melanoma, basal cell carcinoma and prostate cancer; suggestive association with sarcoma/fibrosarcoma and Hodgkin’s lymphoma/Hodgkin’s disease). In addition, we found the GRS was suggestively associated with an increased risk of leukemia. In the TCGA dataset we observed suggestive evidence that the GRS was associated with high death hazard of rectum adenocarcinoma (READ), sarcoma (SARC) and skin cutaneous melanoma (SKCM); while the GRS was associated with low death hazard of kidney renal papillary cell carcinoma (KIRP). The results of MR further supported the association for leukocyte telomere length on the risk of malignant melanoma, Hodgkin’s lymphoma/Hodgkin’s disease, chronic lymphocytic leukemia and multiple myeloma. Conclusions: Our study reveals that telomere played diverse roles in different types of cancers. However, further validations in large scale prospective studies and deeper investigations of the biologic mechanisms are warranted.